Pharmacological and phytochemical screening of Desmodium gangeticum and Moringa oleifera - Preeti S.; Gaurava S. (My University, 2025)
Desmodium gangeticum and Moringa oleifera are medicinal plants, with diverse medicinal and health related benefits. The major objective of present study was to evaluate phytochemical profile of D. gangeticum and M. oleifera. Common phytochemicals of D. gangeticum and M. oleifera were estimated using standard tests and reported with their presence and/or absence. The phytochemical analysis carried out on D. gangeticum and M. oleifera leaves showed the presence of variety of active compounds including alkaloids, tannins, phenols, flavonoids, terpenoids, tannins in both whereas saponins and volatile oils were absent in D. gangeticum and carbohydrates was absent in M. oleifera. The major constituents responsible for the pharmacological properties of these plant have been determined, but still the molecular mechanisms of most of the principles of these plants are incomplete. Future work should be moving on for better identification and isolation of another novel compound/s. All these preliminary reports warrant an in-depth analysis of the usefulness of these two plants as drug against various ailments and diseases. © 2018 International Congress of Chemistry and Environment. All Rights Reserved.